Teaching models and local-area networks - Brant Parker; Tom Jones (Association for Learning Technology, 1994)
The thesis of this paper is that new advances in both microtechnology and LAN technology can now provide teachers with flexible and exciting instructional tools which allow for a powerful integration of teaching model, curriculum content and technology. The first section describes some of the current applications of school-based LANs. The second section discusses various teaching models, and describes an in-depth example of how a teacher may go about providing instruction by combining a LAN and these models. The third section addresses the feasibility of such an instructional approach.